Analisis Kebutuhan Hierarki Abraham Maslow Terhadap Tokoh Rebecca Pada Novel Dear Nathan-Hello Salma Karya Erisca Febriani - Aisyah Nur Shahara; Ranfa Kinanti; Eva Dwi Kurniwan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study aims to analyze the self-actualization of Rebecca's character in the novel entitled "Dear Nathan-Hello Salma" using Abraham Maslow's hierarchy of needs theory, which has five levels of needs namely physiololgis, security, affection, self-esteem and self-actualization. By using descriptive qualitative research methods, analyzing the life of Rebecca's character in building self-confidence after going through a problem that almost made her give up on life. The results of the study show that the five hierarchical needs of Rebecca have been fulfilled entirely in sequence starting from the needs at the lowest level to the highest level. Namely from physiological needs, then the need for security, the need for love and existence, the need for appreciation and the last is the need for self-actualization.